Factors Influencing Manipulation of a Familiar Object in Patients With Limb Apraxia After Stroke - Pizzamiglio, Gloria; Zhang, Zuo; Duta, Mihaela; Rounis, Elisabeth (Frontiers in Human Neuroscience, 2020)
Previous studies have shown that hand actions to visual objects are affected both by perceptual factors and by action goals. Our aim was to study how these processes affected hand actions in chronic stroke patients, based on whether they had limb apraxia. Twenty-two left hemisphere, chronic stroke patients were measured on neuropsychological tasks of limb apraxia, which was identified in a subgroup of 10 patients. All patients underwent testing on a separate task of making simple reach and grasp actions to a cup. Their performance was compared to a group of 18 healthy age-matched volunteers. Participants were instructed to grasp the top or bottom of a cup to either lift or turn it over so as to end with a hand position that was either comfortable or uncomfortable. This task tested the influence of the compatibility of hand–cup orientation, as well as goals driven by the end-state comfort of the hand, on action selection for object manipulation. Participants’ performance was measured in terms of error rates, and speed of initiation and reaching (movement time) to the object. The patients’ performance was significantly delayed, and error rates increased when reaching to grasp a cup under conditions of poor compatibility and end-state comfort. The subgroup of patients with apraxia showed a decreased influence of compatibility of hand interaction with the cup, with increased error rates and delayed response times, compared to patients with no apraxia and healthy volunteers. This is despite the fact they did not display significant deficits on neuropsychological tasks of real object use. The study shows that patients with apraxia have difficulties in selecting elements of object-directed actions, pertaining to both habitual and goal-directed factors.